Home Range of Lomas Lizard Microlophus tigris (Sauria: Tropiduridae) in Carabayllo Lomas, Lima - Peru - Ruiz S., Jorge (2017)
The home range is the area where an individual finds the resources for its survival; therefore, the home range studies of organisms are fundamental to know their ecology and conservation status. The Loma’s lizard, Microlophus tigris is an endemic species of Peruvian central coast, whose home range has not been studied. We used the Minimum Convex Polygon method on 15 individuals (9 males and 6 females) to estimate the home range of M. tigris during the non-breeding season in Lomas de Carabayllo, Lima, Peru. We found males were significantly larger and heavier than females. However, there were no significant differences between male and female home ranges due to high variability in males. The home range size of the evaluated lizards was not related to their body size (snout vent-length) or their weight. The lack of relation between home range and the analyzed variables suggests that the home range size of M. tigris, during the non-breeding season, may be related to other parameters such as resource availability or climatic conditions. The low home range overlap between and among sexes, indirectly indicates there is territorial behavior. According to our data and natural history information of other species of lizards, we believe there may be variation in the spatial use during other seasons. Therefore, it is necessary complementary evaluations to observe other relevant factors that define home range of M. tigris.